Antimicrobial and antileishmanial activities of diterpenoids isolated from the roots of salvia deserta - Búfalo, Jennifer [UNESP]; Cantrell, Charles L.; Jacob, Melissa R.; Schrader, Kevin K.; Tekwani, Babu L.; Kustova, Tatyana S.; Ali, Abbas; Boaro, Carmen S. F. [UNESP] (Georg Thieme Verlag KG Stuttgart · New York., 2015)
Four diterpenes with biological activity were isolated from Salvia deserta roots. Taxodione was considered leishmanicidal with an IC50 value of 1.46 µM (0.46 mg/L) against Leishmania donovani and also exhibited antifungal and antimicrobial activities. Ferruginol displayed the greatest activity [24-h IC50 of 4.5 µM (1.29 mg/L)] against the fish pathogenic bacteria Streptococcus iniae. The crude extract fraction that contained the isolated compounds 7-O-acetylhorminone and horminone showed stronger in vitro antibacterial activity (1.3 mg/L for Staphylococcus aureus and 1.1 mg/L for methicillin-resistant S. aureus) than the compounds tested alone. 7-O-Acetylhorminone and horminone exhibited a synergistic effect against methicillin-resistant S. aureus (FIC of 0.2), and horminone had better activity against S. aureus with respect to other compounds isolated from S. deserta roots. In larvicidal bioassays, these extracts and isolated pure compounds did not show any activity at the highest dose of 125 mg/L against 1-d-old Aedes aegypti larvae.
Keywords: Salvia deserta; Lamiaceae; Diterpenoid; Leishmania; Antimicrobial activity; Staphylococcus aureus; Streptococcus iniae